Internal Auditory Canal Diverticula in Children: A Congenital Variant. (17th November 2020) - Muelleman, Thomas J.; Kavookjian, Hannah; Asmar, Julia; Patel, Kirang; Nielsen, David; Summers, Kyle; Tracy, Meghan; Noel‐MacDonnell, Janelle; Staecker, Hinrich; Ledbetter, Luke; Weatherly, Robert
Abstract : Objectives/Hypothesis: Internal auditory diverticula in adults have been found to exist independent of otosclerosis, and in the presence of otosclerosis. We sought to determine the prevalence of internal auditory canal (IAC) diverticula in a pediatric cohort, to assess whether IAC diverticula are a risk factor for hearing loss, and the co‐occurrence of otic capsule hypoattenuation. Study Design: Retrospective review. Methods: A single‐site retrospective review of high‐resolution temporal bones computed tomography (CT) scans including the presence and size of diverticula and hypoattenuation of the otic capsule. Demographic, imaging, and audiometric data were collected and descriptively analyzed. Bivariate analysis of collected variables was conducted. Comparisons between sides in unilateral cases were also performed. Results: 16/600 (2.7%; 95% CI [2.0%, 3.4%]) were found to have IAC diverticula. Six were bilateral. Thirty‐one patients (5.2%) were found to have hypoattenuation of the otic capsule. There were no coincident cases of IAC diverticulum and hypoattenuation of the otic capsule. There was no association between the presence of IAC diverticula and age ( P = .13). In six patients with unilateral diverticula, pure tone average ( P = .42), and word recognition ( P = .27) scores were not significantly different when compared to the normal, contralateral side. Conclusions: The prevalence of IAC diverticula in children is lower than the prevalence in adults. IAC diverticula in children likely represent congenital variants of temporal bone anatomy. Similar to adult populations, there is evidence that IAC diverticula in children are likely not an independent risk factor for hearing loss. Level of Evidence: 4 Laryngoscope, 131:E1683–E1687, 2021